Veer ecology : a companion for environmental thinking - Cohen, Jeffrey Jerome; Duckert, Lowell, 1982- (University of Minnesota Press, 2017)
The words most commonly associated with the environmental movement-save, recycle, reuse, protect, regulate, restore-describe what we can do to help the environment, but few suggest how we might transform ourselves to better navigate the sudden turns of the late Anthropocene. Which words can help us to veer conceptually along with drastic environmental flux? Jeffrey Jerome Cohen and Lowell Duckert asked thirty brilliant thinkers to each propose one verb that stresses the forceful potential of inquiry, weather, biomes, apprehensions, and desires to swerve and sheer. Each term is accompanied by a concise essay contextualizing its meaning in times of resource depletion, environmental degradation, and global climate change. Some verbs are closely tied to natural processes: compost, saturate, seep, rain, shade, sediment, vegetate, environ. Many are vaguely unsettling: drown, unmoor, obsolesce, power down, haunt. Others are enigmatic or counterintuitive: curl, globalize, commodify, ape, whirl. And while several verbs pertain to human affect and action-love, represent, behold, wait, try, attune, play, remember, decorate, tend, hope-a primary goal of Veer Ecology is to decenter the human. Indeed, each of the essays speaks to a heightened sense of possibility, awakening our imaginations and inviting us to think the world anew from radically different perspectives. A groundbreaking guide for the twenty-first century, Veer Ecology foregrounds the risks and potentialities of living on-and with-an alarmingly dynamic planet.